Pengaruh Kompensasi, Motivasi, dan Lingkungan Kerja terhadap Kinerja Karyawan PT Surgika Alkesindo - Wildan Muzaqi; Ai Netty Sumidartini (JAMBIS : Jurnal Administrasi Bisnis, 2023)
Every company always expects every employee to have achievements, because employees who excel will make an optimal contribution to the company. Superior and quality performance can be obtained if the company is able to contribute to employees as compensation for the company's services to its employees. In addition, the performance of an organization will increase if there is motivation and a good work environment from the organization itself. The method used in this research is descriptive quantitative, the population in this study are employees of PT Surgika Alkesindo. The number of samples used in this study were 99 people. The effect of Compensation (X1) on Performance (Y) is 0.000 <0.05 and the value of Tcount > Ttable is 3.894 > 1.895, then Ho1 is rejected and Ha1 is accepted, the partial effect is 9.2%. The effect of Motivation (X2) on Performance (Y) is 0.000 < 0.05 and the value of Tcount > Ttable is 8.734 > 1.895 then Ho2 is rejected and Ha2 is accepted, the partial effect is 60.4%, and the influence of the Work Environment (X3) on Performance (Y) is 0.011 < 0.05 and the value of Tcount > Ttable is 2.593 > 1.895, then Ho3 is rejected and Ha3 is accepted, the partial effect is 6.3%. Effect of Compensation (X1), Motivation (X2) and Work Environment (X3) on Performance (Y) is Fcount 169.011 > Ftable 2.70, then Ho4 is rejected and Ha4 is accepted. There is an effect of Compensation, Motivation and Work Environment simultaneously on Performance significantly at PT Surgika Alkesindo by 84.2